تأثير منهج إرشادي معرفي سلوكي في الحد من سلوك العنف الجامعي لدى طلاب المرحلة الرابعة في كلية التربية الرياضية / جامعة صلاح الدين - السلطاني, عظمية (Sulaimani Journal for Humanities, 2018)
Given the experience of the researcher Ktdiricih and follow-up of the process of study at the university, I have noticed a growing and doubled the phenomenon of violence among the students of the Faculty of Physical Education, especially the fourth stage students and significantly, it may be due to lack of monitoring and inadequate penalties for wrong behaviors, as well as the weakness of adhering to the values and societal habits related to the subject, in addition to the lack of sufficient area to guide students to the desired behavior, and to be followed in dealing with professors and colleagues, and the weakness of expertise or adequate theories and techniques of psychological counseling know-how it has treated some of the teachers with the problems that occur with the students, all of these reasons lead to the growing phenomenon of violence.